2021
DOI: 10.1038/s41467-021-24936-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and selectivity of CO2 reduction to CO on gold gas diffusion electrodes in acidic media

Abstract: The electrochemical reduction of CO2 to CO is a promising technology for replacing production processes employing fossil fuels. Still, low energy efficiencies hinder the production of CO at commercial scale. CO2 electrolysis has mainly been performed in neutral or alkaline media, but recent fundamental work shows that high selectivities for CO can also be achieved in acidic media. Therefore, we investigate the feasibility of CO2 electrolysis at pH 2–4 at indrustrially relevant conditions, using 10 cm2 gold gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(153 citation statements)
references
References 27 publications
2
151
0
Order By: Relevance
“…Importantly, the excess protons provided in this system are not linked to the current density applied, implying that different optimal input acidities and flow rates are required for different current densities. A more recent work was able to reach higher FEs of ∼90% for CO 2 to CO on Au in acidic media, 15 but the maximum utilizations achievable and homogeneous reactions were not discussed. It is then unclear if these demonstrated high FEs can be simultaneously achieved with high utilizations.…”
mentioning
confidence: 99%
“…Importantly, the excess protons provided in this system are not linked to the current density applied, implying that different optimal input acidities and flow rates are required for different current densities. A more recent work was able to reach higher FEs of ∼90% for CO 2 to CO on Au in acidic media, 15 but the maximum utilizations achievable and homogeneous reactions were not discussed. It is then unclear if these demonstrated high FEs can be simultaneously achieved with high utilizations.…”
mentioning
confidence: 99%
“…Along the same line, we recently reported on the selectivity and efficiency of CO 2 reduction to CO in acidic media on 10 cm 2 Au-GDEs with different loadings. 14 In galvanostatic measurements, we observed slightly improved selectivity for CO with the GDE having lower catalyst loading (1 mg cm −2 ) than the one with higher loading (2 mg cm −2 ). Through scanning electron microscopy (SEM) analysis of the two GDEs, we attributed those differences to agglomerates within the catalyst layer at a loading of 2 mg cm −2 , which prevents access of the reactants to the catalyst nanoparticle surface.…”
Section: Introductionmentioning
confidence: 74%
“…3b and 5 ). For example, we previously performed experiments with a large excess of CO 2 , and the GDE with lower catalyst loading exhibited a higher faradaic efficiency for CO. 14 On the other hand, Duarte et al 6 observed an increase in CO partial current density with increasing loading but with no effect on the faradaic efficiency. This also points out to the fact that different gas diffusion layers highly differ in terms of how the pore channels are distributed and how permeable and hydrophobic the layer is.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we assessed the energy cost of the sequential route based on future CO2 gas-fed electrolysis with no carbonate formation. Very recent reports demonstrated the potential to improve CO2 utilisation efficiency 41 by developing catalyst-membrane interface 35,42 , optimising cell operating conditions (e.g., reducing CO2 flow rates, increasing current densities, and optimising anolyte compositions and ionic strength) 37 , or supplying protons towards the cathode to regenerate CO2 from the (bi)carbonates, e.g., flowing strong acidic catholyte 20,43 , applying cation-exchange membranes 35 or bipolar membrane 42 in a reverse mode. The single-pass conversion rate remains 50% in this optimistic sequential model, meaning that 50% of the inputted CO2 feed converts to CO product and reduces the required pressureswing absorption separation energy cost.…”
Section: Fig 3 Scenario Analysis Of Overall Energy Cost For Sequential and Integrated Routesmentioning
confidence: 99%